Labour incentive reforms in preretirement age in Austria - Edlira Narazani; Isilda Shima (University of Essex, Institute for Social and Economic Research (ISER), 2009)
In view of the political debate on the future sustainability of pensions system in Austria and given the low participation of older worker in the labour market, in this paper we try to shed light on employment and retirement behaviour while a combination of reduction in pension benefits along with income support is provided. We find out that reforms characterized by moderately generous income support while working along with lower pension entitlement in early retirement yield higher social welfare compared to the current system. The labour supply response signals increase under the proposed reforms among middle-income males, in the age category 55-60, whereas these reforms seem to be ineffective for women. These findings emphasize the importance of introducing pension reforms complemented with tax-benefits policies such that the former remove the disincentives to retire earlier and the later enhance the employment of workers in preretirement age.
Keywords: 330; supply; discrete choice models; guaranteed minimum income; retirement; older worker; Gesetzliche Rentenversicherung; Altersgrenze; Ältere Arbeitskräfte; Mindestlohn; Arbeitsangebot; Österreich